Judicial Review of Criminal Liability of Doctors for Malpractice - Sandra, Gustika; Panji, Andi (Journal of Indonesian Scholars for Social Research, 2022)
This study aims to determine the liability of medical malpractice by doctors. This research was conducted with a qualitative approach, using descriptive analysis; the aim is to study and find facts to be used for further investigation. This research was conducted at Hapsah Hospital, Bone Regency. Data analysis by concluding inductively. The study results show that the hospital's responsibilities and sanctions if proven professional wrongdoing can be punished by revocation of practice licenses and must provide compensation to patients and family members, but from a legal point of view. The general laws and regulations related to criminal acts, namely the Code of Criminal Law Number 29 of 2004 concerning Medical Practice and various other laws and regulations, including the Decree of the Minister of Health of the Republic of Indonesia Number 434 / MEN.KES / SK / X / 1993 concerning the Ratification and Implementation of Indonesian Medical Law.